answersLogoWhite

0


Best Answer

1)5r+7=13+2r+3r

2)5r+7=13+5r

3)5r's cancel

7=13

4)Subtract thirteen on both sides

7 =13

-13 -13

5)Answer is no solution because -6 doesn't equal to 0.

-6=0

NO SOLUTION!!!

Have fun with math!

User Avatar

Wiki User

โˆ™ 2012-02-02 00:25:27
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is 5r plus 7 equals 13 plus 2r plus 3r?
Write your answer...
Submit
Related questions

What is 32 plus 3r equals 82-2r?

A math problem


Can r plus 2r - 3r be simplified?

5


13r plus 10 equals 5r-46?

3r+10=5r-46 --> add 46 to both sides 3r+10+46=5r-46+46 3r+56=5r --> subtract 3r from both sides 3r+56-3r=5r-3r 56=2r --> divide both sides by 2 56/2=2r/2 28=r


Factor the polynomial -18r to the power of 3 plus 242r?

-2r(3r - 11)(3r + 11)


What is 3r-8 equals2-2r?

If: 3r-8 = 2-2r Then: 5r = 10 And: r = 2


8 plus 2 8r-2r 4 3r plus 2 r 0 is the only solutionis this correct?

It is not correct to say that 8 plus 2 8r-2r 4 3r plus 2 r = 0


3r plus 6-6 equals 2r-12-6?

No, it's simply 3r, because multiplication (r multiplied by 3) comes first in the order of operations.


R plus 3 plus 2r equals - 21?

r+3+2r=21 to solver this equation you have to first simplify then solve. you have to combine same variables. 3r+3=21 -3 -3 you subtract three to get r by itself (3r=18)/3 you divide by three to get r by itself Answer r=6


How do you Factor 3r squared equals 13r plus 10?

(3r + 2)(r - 5)


How do you solve the equation 17 equals 13-3r?

17 = 13 - 3r Subtract 13 from bith sides: 4 = -3r Divide both sides by -3 : -4/3 = r or r = -1.3...


How do you factor 6r2-87r plus 270?

6r2-87r+270 = (2r-9)(3r-30) when factored


What is the factor for 3r to the power of 2 - 2r - 5?

(r + 1)(3r - 5)


How do you solve 7r equals 3r-52?

7r = 3r - 527r (- 3r) = 3r - 52 (- 3r)4r = - 524r / 4 = -52 / 4r = -13


What is the answer to 3r plus 3r plus 2t?

3r + 3r + 2t = 6r + 2t


What is -5 equals 7 plus 3r?

If: -5 = 7+3r then the value of r works out as -4


What is the sum of r - 10 and 100 - 3r?

r - 10 + 100 - 3r = -2r + 90


What is r in this equation and how do you do it minus 5 equals 7 plus 3r?

-5 = 7 + 3r | subtract 7 -12 = 3r | divide by 3 -4 = r


What is the answer of 9r equals 3r plus 6?

9r = 3r + 6 subtract 3r from both sides 6r = 6 divide both sides by 6 r=1 ■


Which pair of values is the solution to the system of equations below r plus 2t equals -3 and 3r-4t equals -9?

r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)


What is -3r-13 r equals 2 is?

-16r=2 divide both sides by -16 and your answer is -1/8


What is the radix of the number if the solution to quadratic equation x2-10x plus 31 equals 0is x equals 5and x equals 8?

Solution:(5r0)2 - (1r1+0r0)*5 + 3r1+1r0 = (8r0)2 - (1r1+0r0)*8 + 3r1+1r0 25 - 5r + 3r + 1 = 64 - 8r + 3r + 13r - 39 = 0r = 13Result: radix r = 13


How can you find the first term of an arithmetic sequence if you know the third and fifth terms?

Suppose A is the first term and R is common difference. Then, if t(n) is the nth term, t(n) = A + n*R Then t(5) = A + 5R and t(3) = A + 3R so that t(5) - t(3) = 2R Now t(1) = A + R = A + 3R - 2R (since R = 3R - 2R) So t(1) = t(3) - 2R You were given t(3) and have calculated 2R above, so can work out t(1).


How do you work out the problem 9r equals 3r plus 6?

9r = 3r+6 Subtract 3r from both sides: 6r = 6 Divide both sides by 6 to find the value of r: r = 1


What are the factors of 3r plus 12?

3r + 12 = 3*(r+4)


How do you factor 9r squared minus 12r plus 4?

(3r - 2)(3r - 2) or (3r - 2) squared.